2016
DOI: 10.3390/sym8040020
|View full text |Cite
|
Sign up to set email alerts
|

Resource Symmetric Dispatch Model for Internet of Things on Advanced Logistics

Abstract: Business applications in advanced logistics service are highly concurrent. In this paper, we propose a resource symmetric dispatch model for the concurrent and cooperative tasks of the Internet of Things. In the model, the terminals receive and deliver commands, data, and information with mobile networks, wireless networks, and sensor networks. The data and information are classified and processed by the clustering servers in the cloud service platform. The cluster service, resource dispatch, and load balance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Software must meet a market window set by competitive organizations. High-quality software that meets the requirements of the process to be served with minimal failure and maximum security [10][11][12][13][14]. Nonetheless, several studies have reported different challenges in implementing CBSD.…”
Section: Introductionmentioning
confidence: 99%
“…Software must meet a market window set by competitive organizations. High-quality software that meets the requirements of the process to be served with minimal failure and maximum security [10][11][12][13][14]. Nonetheless, several studies have reported different challenges in implementing CBSD.…”
Section: Introductionmentioning
confidence: 99%
“…The Internet of Things (IoT) [1][2][3][4] uses smart equipment such as sensor-based devices [5][6][7][8][9][10][11], smartphones [12] and vehicle sensor devices [13] to gathering information and give a different method for carrying out complex data-sensing-based tasks to satisfy the significant demands of critical infrastructures [14][15][16][17][18], such as environmental and weather monitoring systems [19][20][21][22][23]. Wireless Sensor Networks (WSNs) has large numbers of sensor nodes, it has huge potential to solve military and civilian domains [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%